2017
DOI: 10.1080/17496535.2017.1375134
|View full text |Cite
|
Sign up to set email alerts
|

Embodied Austerity: Narratives of Early Austerity from a Homelessness and Resettlement Service

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The results add to the existing literature which considers the impact of working within an increasingly inflexible and target-driven environment in the context of the austerity agenda and market-driven approaches to service provision (Banks, 2011; Renedo, 2014). In line with findings by Daly (2017), project workers’ identity as an advocate and helper was often compromised, through being placed in a position of deciding “deservedness” for limited resources; or not having the means to focus on residents’ emotional needs. Reynolds (2012) describes the “spiritual or ethical pain” prompted when practicing in accordance with one’s values is violated by the working context.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The results add to the existing literature which considers the impact of working within an increasingly inflexible and target-driven environment in the context of the austerity agenda and market-driven approaches to service provision (Banks, 2011; Renedo, 2014). In line with findings by Daly (2017), project workers’ identity as an advocate and helper was often compromised, through being placed in a position of deciding “deservedness” for limited resources; or not having the means to focus on residents’ emotional needs. Reynolds (2012) describes the “spiritual or ethical pain” prompted when practicing in accordance with one’s values is violated by the working context.…”
Section: Discussionmentioning
confidence: 60%
“…In recent years the UK government’s austerity programme has become “embodied” in ethics and practices of care, impacting on relationships between workers and PEH (Daly, 2017). With budget cuts across the sector, market-driven approaches to service provision have led to practice guidance becoming increasingly inflexible, with “success” defined via output and targets (Renedo, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the contemporary neoliberal sociopolitical context, additional barriers related to attending to care and justice within community settings abound. Austerity measures and welfare reform both create severe limitations on budgeting for needed care, and create challenging and devaluing environments for workers in the care sector (Daly, 2018; Gist‐Mackey & Guy, 2019; Lydahl & Hansen Löfstrand, 2020). Furthermore, those interested in caring for individuals perceived as in need may rely on assumptions or stereotypes, particularly when aiming to work with communities of which one is not a part (Little, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This paper addresses this call by exploring the impact of austerity policies in the homelessness field offers the perspectives of homelessness practitioners specifically in relation to the adverse impact of austerity and welfare reform on the well-being of homelessness practitioners (Daly, 2018). The analysis of the service providers’ data revealed that they have witnessed the structural violence of austerity that their clients face with the welfare system changes.…”
Section: Discussionmentioning
confidence: 99%